Determinan Efisiensi Bank Umum Syariah di Indonesia dengan Profitabilitas sebagai Pemoderasi - Venny Darlis; Triana Utary (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
This paper explores the Effect of Asset Diversification, Capital Adequacy Ratio (CAR), Credit Risk, and Liquidity on the Efficiency of Islamic Commercial Banks in Indonesia with Profitability as Moderating Variable and Bank Size as Control Variable during 2014-2018 .Based on the purposive sampling method, 12 banks were selected. This study uses multiple linear regression as a method of data analysis. The results showed that asset diversification and credit risk moderated by profitability had an insignificant negative effect on efficiency. Credit risk and CAR had an insignificant positive effect on efficiency. Meannwhile liquidity, capital adequacy ratio moderated by profitability have significant negative effect on efficiency,. Furthermore, asset diversification moderated by profitability, Liquidity moderated by profitability, and Bank Size (Size) have a significant positive effect on efficiency. The results of this study are expected to be a reference regarding the efficiency of Islamic commercial banks.